Pengaruh Viral Marketing dan Harga Terhadap Keputusan Pembelian King Shoes Bali Melalui Media Sosial Instagram - Ni Kadek Citra Anggreni; I Nyoman Sujana (Ekuitas: Jurnal Pendidikan Ekonomi, 2025)
This study aims to analyze: (1) the influence of viral marketing on purchase decisions, (2) the influence of price on purchase decisions, and (3) the simultaneous influence of viral marketing and price on purchase decisions. The population in this study includes all consumers who have made purchases at King Shoes Bali. Since the exact number of consumers is unknown, the population is categorized as an unknown population. The sampling technique used is purposive sampling, with a total of 120 respondents determined based on the number of indicators used. Data were collected through questionnaires and analyzed using multiple linear regression, with hypothesis testing conducted through t-tests and F-tests using SPSS version 16 software. The results show that: (1) viral marketing has a positive and significant effect on purchase decisions at King Shoes Bali through Instagram, (2) price also has a positive and significant effect on purchase decisions at King Shoes Bali through Instagram, and (3) simultaneously, viral marketing and price together have a positive and significant effect on consumer purchase decisions at King Shoes Bali through Instagram